Antiplanktonic, antibiofilm, antiswarming motility and antiquorum sensing activities of green synthesized Ag–TiO2, TiO2–Ag, Ag–Cu and Cu–Ag nanocomposites against multi-drug-resistant bacteria. (12th November 2018) - Alavi, Mehran; Karimi, Naser
Abstract: Fighting of current antibiotics against multidrug-resistant (MDR) bacteria has not been completely successful. In this study, the bio-synthesized Ag–TiO2, TiO2 –Ag, Ag–Cu and Cu–Ag nanocomposites (NCs) were used against MDR bacteria including Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853 (gram negative) and Staphylococcus aureus ATCC 43300 (gram positive). Antiplanktonic, antibiofilm, antiswarming motility and antiquorum sensing activities of these four NCs were measured by assays of agar well diffusion, minimum inhibition/minimum bactericidal concentrations (MIC/MBC), biofilm formation, biofilm morphology and pyocyanin amounts. Agar well diffusion method illustrated higher inhibition zone diameter (IZD) of Ag-TiO2 NCs with 13 ± 1, 16 ± 1.73 and 21.66 ± 1.52 mm against E. coli ATCC 25922, S. aureus ATCC 43300 and P. aeruginosa ATCC 27853 respectively. Swarming motility of P. aeruginosa at presence of NCs demonstrated lower density than control samples. Ordering of antibiofilm strength for these NCs was Ag–TiO2 > TiO2 –Ag > Cu–Ag > Ag–Cu. In addition, biofilm roughness and also pyocyanin synthesis as virulence factor related to quorum sensing mechanisms of P. aeruginosa ATCC 27853 was decreased under Ag–TiO2 NCs. In total, the present investigation illustrated eco-friendly and one-pot way to synthesize metal NCs with having significant antibacterial, antibiofilm and antiquorum sensing abilities.